Polysaccharide-Silica Hybrids: Design and Applications. (2nd January 2016) - Singh, Vandana; Srivastava, Preeti; Singh, Angela; Singh, Devendra; Malviya, Tulika
Abstract : This article discusses and reviews the current status and future perspectives of silica hybrids of polysaccharides and biosilicas derived thereof. The hybrids have been produced in various morphological shapes and utilized in water remediation, separation, enzyme immobilization, sensor, and biomedical fields. The polysaccharides show templating and structure directing influence in manipulation of sol gel silica hybrid materials which can be calcined to derive functional biosilicas. The development of energy storage devices and white light emitting solid phosphors may be the fields of future research.